Biomineralization of struvite induced by indigenous marine bacteria of the genus Alteromonas - He, Wei; Xue, Hua-Peng; Liu, Chuang; Zhang, Ai Hua; Huang, Jian-Ke; Zhang, Dao-Feng (Frontiers in Marine Science, 2023)
Abstract Biomineralization is a universal phenomenon in the ocean, which played an important role in the marine geochemical circulation. The genus Alteromonas is an indigenous taxon with wide distribution and various ecological roles in the ocean, but biomineralization of this genus has not been reported. In this study, five Alteromonas spp. were found to induce mineral crystals of different shapes and sizes in agar media. Further studies on deep-sea strains A. alteriprofundi HHU 13199T and A. alterisediminis N102T showed that they could produce mineral crystals with similar morphology in agar or broth media with different sea salt concentrations (2%, 4%, 6%, 8%) and their growth was dependent on Ca2+ and/or Mg2+ ion concentrations. The genomic analysis showed that the genus Alteromonas universally possessed the ammonification metabolism pathway, and during the culturing of bacteria, the production of mineral crystals was accompanied by an increase in ammonia concentration and pH value and decrease in nitrate nitrogen concentration. The addition of ammonia to the broth media (~572.7 mg/L) simulated ammonia content in medium at 5~6th day of bacterial growth and also induced mineral crystals. Through the analysis of scanning electron microscope-energy dispersive spectrometry (SEM-EDS), X-ray diffractometer (XRD), fourier transform infrared microscopy (FTIR), thermogravimetric (TG), differential thermal gravity and differential scanning calorimetry (DTG-DSC), mineral crystals induced by bacterial strains and non-strain (ammonia-added sample) were all identified as struvite mineral, and the characteristics of struvite mineral induced by bacterial strains were different from that synthesized by non-strain and struvite mineral standard. Thus, this study deduces that Alteromonas spp. possess the ability to induce struvite minerals, and the mechanism mainly lies in the prevalence of an ammonification metabolism pathway to produce ammonia, which should be recognized as biologically-induced mineralization. This study provides insight into a new ecological role of indigenous marine taxon of the genus Alteromonas.